BMP-4 and fetuin A in systemic sclerosis patients with or without calcinosis - Lofaro, Francesco Demetrio; Giuggioli, Dilia; Bonacorsi, Susanna; Orlandi, Martina; Spinella, Amelia; De Pinto, Marco; Secchi, Ottavio; Ferri, Clodoveo; Boraldi, Federica (Frontiers in Immunology, 2024)
IntroductionSystemic sclerosis (SSc) is a connective tissue disease at the interface between inflammation and autoimmunity progressively leading to diffuse microvascular and fibrotic involvement of the skin and of multiple internal organs. Approximately, 20-40% of SSc patients suffer from cutaneous calcinosis, a debilitating manifestation due to calcium salt deposition in soft connective tissues, causing pain, ulceration, infection, and deformities, responsible of severe functional limitations. Pathomechanisms are poorly understood as well as markers/molecules capable to predict the risk of patients to develop calcinosis.MethodsAn observational study was performed in 51 female patients, 25 with and 26 without calcinosis to compare clinical and laboratory parameters and to evaluate pro- and anti-calcifying circulating markers and the in vitro serum calcification potential (T50). Moreover, calcinosis samples were analyzed to characterize their mineral composition.Results and discussionData demonstrate statistically significant differences in the prevalence of clinical manifestations and ACA and Scl70 autoantibodies in SSc patient with calcinosis compared to those without calcinosis. In SSc patients with calcinosis, serum levels of BMP-4 are higher, fetuin A might be regarded as a potential circulating prognostic marker and a negative correlation was observed between T50 and the global score of clinical manifestations, suggesting a potential predictive role of pro- and anti-calcifying molecules in SSc patients. Furthermore, calcinosis samples were characterized by the co-existence of phosphate and carbonate minerals with different stability and solubility. Further investigations on circulating markers in larger patient cohorts, especially at the early stages and throughout the natural course of the disease, may clarify their pathogenetic role in the SSc-related cutaneous calcinosis.